Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1600-0684.2010.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rectal and tympanic core body temperature measurement in adult Guyanese squirrel monkeys (Saimiri sciureus sciureus)

Abstract: The tympanic thermometer designed for use in humans can be used in adult squirrel monkeys as an alternative to rectal thermometry for assessing core body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In our captive adult black tufted‐ear marmosets, basal thermal values obtained via RC and SC routes were significantly higher than those recorded at the left and right TM. The former two had equivalent temperature ranges and were similar to values reported for neotropical primates, including marmosets . RC data reflect deep body temperatures, which in turn are usually higher than those detected at more superficial levels [e.g., ].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In our captive adult black tufted‐ear marmosets, basal thermal values obtained via RC and SC routes were significantly higher than those recorded at the left and right TM. The former two had equivalent temperature ranges and were similar to values reported for neotropical primates, including marmosets . RC data reflect deep body temperatures, which in turn are usually higher than those detected at more superficial levels [e.g., ].…”
Section: Discussionsupporting
confidence: 65%
“…It is also important to point out that the thermal values recorded at the left and right TM were similar in range, yet lower than previous reports for this species . While the former result initially suggests a symmetrical cerebral activation during the procedure , pre‐capture baseline TM temperatures are not available and thus individual differences may confound this effect . In addition, the individuals assessed in the present study have an extensive capture and manipulation history due to clinical and experimental procedures (>20 events), which may have led to higher neural activation, brain temperatures, and blood flow, and thus lower TM temperatures .…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In veterinary medicine, auricular thermometry has been investigated in several species, including dogs, cats, non-human primates and various other laboratory animals. 5,8,9,15,16 In general, these studies indicate that animals tend to tolerate the use of these devices more readily than rectal thermometers. However, the results regarding correlation with an established method of measuring temperature are somewhat contrasting.…”
Section: Discussionmentioning
confidence: 98%
“…7 Studies in veterinary medicine have demonstrated contrasting results, 1,5,8,9 with the majority of them concluding that auricular and rectal temperatures cannot be used interchangeably.…”
Section: Introductionmentioning
confidence: 99%